2008
DOI: 10.1016/j.exer.2008.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Elevated amounts of myocilin in the aqueous humor of transgenic mice cause significant changes in ocular gene expression

Abstract: Myocilin is a 55-57kDa secreted glycoprotein and member of the olfactomedin family, which is mutated in some forms of primary open-angle glaucoma. To assess the effects of elevated amounts of myocilin on aqueous humor outflow dynamics in an in vivo system, transgenic betaB1-crystallin-MYOC mice have been developed that strongly overexpress myocilin in their eyes. The transgenic overexpression of myocilin results in an almost five-fold increase of secreted normal myocilin in the aqueous humor of betaB1-crystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 67 publications
1
19
0
Order By: Relevance
“…Studies on steroid-induced glaucoma have shown that TAA and Dex induce dose dependent, differential gene profiles in human trabecular meshwork (TM) cells, revealed by microarray technology 18-21 . Today, the TM epithelium is considered to be the target tissue and the myocilin gene, expressed mainly in TM, the top candidate gene for the development of steroidinduced glaucoma, through the proposed mechanism of increased intraocular pressure (IOP) 22 . Although an elevated IOP is a significant risk factor for the development of glaucoma, it is important to note that sight-threatening effects of glaucoma are not necessarily coming from increased IOP but from retinal and optic nerve neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on steroid-induced glaucoma have shown that TAA and Dex induce dose dependent, differential gene profiles in human trabecular meshwork (TM) cells, revealed by microarray technology 18-21 . Today, the TM epithelium is considered to be the target tissue and the myocilin gene, expressed mainly in TM, the top candidate gene for the development of steroidinduced glaucoma, through the proposed mechanism of increased intraocular pressure (IOP) 22 . Although an elevated IOP is a significant risk factor for the development of glaucoma, it is important to note that sight-threatening effects of glaucoma are not necessarily coming from increased IOP but from retinal and optic nerve neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…LPHN3 (the latrophilin 3 gene) is a member of the G-protein coupled receptor (GPCR) family; it has large extracellular and intracellular domains, containing several cell adhesion modules, such as cadherin, IgG, laminin A, thrombospondin type 1, galactose lectin, EGF, and transmembrane segments that may be involved in intracellular signalling during cell-to-cell adhesion (Martinez et al, 2011). LPHN3 was up-regulated significantly in a transgenic mice model that over-expressed myocilin (Paper et al, 2008). Altered LPHN3 expression levels have been seen after brain ischemia (Bin et al, 2002), and during the period of adrenal gland development (Wing et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Subjecting the mouse eye to elevated levels of myocilin protein in the aqueous humor also caused changes in the entire eye gene expression. 21 Transgenic mice carrying myocilin cDNA under the control of the bB1-crystallin promoter expressed myocilin in the lens and secreted the protein into the aqueous humor. Transcriptome of the whole mouse eye (minus the lens) was compared to that of the wild-type littermate.…”
Section: Microarraysmentioning
confidence: 99%